OPTIMALISASI JUMLAH BATU BATA YANG PECAH MENGGUNAKAN DESAIN EKSPERIMEN TAGUCHI (Studi Kasus: Usaha Batu Bata Bapak Kholil Ds. Bulak Karangawen) - Cakra Kurniawan; Hasbi Yasin; Sugito Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Brick is a substansial element in building construction. The strength of building may depend on bricks, a solid construction uses the best quality brick’s, which is not crumbling and broken into two parts. There are two popular types of bricks in Semarang, Penggaron bricks and Welahan bricks, Penggaron bricks is the most desirable type in market, but the quality of Penggaron bricks is worse than Welahan bricks, because the Penggaron bricks broken pieces are much more than Welahan’s. So that Penggaron bricks were taken to do research in purpose of optimizing the number of brick’s broken pieces that occurred during the production process. The method being used was the